Под защитой государства - Литвинова Галина Ильинична (В помощь лектору, 1989)
Экземпляры: КХ (20100111) / Инвентарный номер: 0283249 / Цена: 0.15 / Сис.шифр: 67.404.5 / Авт.знак: Л 64 / ГРНТИ: 10 / ББК: 67.404.5